Feminist explanations for the feminization of poverty - Steven Pressman (Luxembourg Income Study (LIS), 2003)
It is well known that women are much more likely to be poor than men. This is true in the US and in most developed nations. But the causes of this phenomenon remain a matter of dispute. This paper looks at two feminist explanations for the feminization of poverty. First, there is the issue of household structure. Second, there is the issue of occupational sex segregation. This paper seeks to examine if either household structure or occupational sex segregation can help explain the relatively high poverty rates experienced by female-headed families.
Keywords: 330; Armut; Frauen; Feministische Ökonomik; USA